1991
DOI: 10.3382/ps.0700935
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet and Population Density on Male Turkeys Under Various Environmental Conditions.

Abstract: Large White Nicholas male turkeys were reared at two stocking densities (.21 or .46 m2 per bird) and fed one of four diets: 1) control corn and soybean (mash) with 1% fat (CSM); 2) as Diet 1, pelleted (CSP); 3) as Diet 1 with supplemental fat increasing from 1 through 8% with age (CSF); and 4) as Diet 1 with barley at 0, 20, 35, 50, and 65% during successive 4-wk periods (CSB). The turkeys were reared in four environments: (A) intermittent light schedule [4(2 h light (L):4 h dark D))] with temperature at 7 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…It is important to note that the highest weight gain occurred in the 18L:6D group, whereas the lowest weight gain was observed in the 12L:12D group in both the first 10 and the last 6 weeks of the study. The results of the feed intake of turkeys are similar to those of other studies in the literature (HALVORSOR et al, 1991;NOLL et al, 1991;CLARKE et al, 1993;SENGUL et al, 2000). On the other hand, maximum live weight difference among three lighting programs throughout first 10 weeks (3473.5 g) was notably higher than the weight gain (2208 g) observed throughout last 6 weeks.…”
Section: Methodssupporting
confidence: 81%
“…It is important to note that the highest weight gain occurred in the 18L:6D group, whereas the lowest weight gain was observed in the 12L:12D group in both the first 10 and the last 6 weeks of the study. The results of the feed intake of turkeys are similar to those of other studies in the literature (HALVORSOR et al, 1991;NOLL et al, 1991;CLARKE et al, 1993;SENGUL et al, 2000). On the other hand, maximum live weight difference among three lighting programs throughout first 10 weeks (3473.5 g) was notably higher than the weight gain (2208 g) observed throughout last 6 weeks.…”
Section: Methodssupporting
confidence: 81%
“…The techniques reported by Ajuyah et al (1991), Halvorson et al (1991), and Izat et al (1991) were selected solely because they were recent papers using commonly reported methods of selecting data. The purpose of this work was not to criticize these authors' works or to question the validity of their data or conclusions, but rather to use their techniques to illustrate potential shortcomings of such practices.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments 1 and 2 essentially duplicate the form of sample truncation used in Ajuyah et al (1991) and Halvorson et al (1991), that of choosing birds closest to the pen means. A third experiment was conducted attempting to duplicate the procedure in Izat et al (1991) as closely as possible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That means sex of the birds had difference response in different density. Halvorson et al (1991) reported that the carcass percentage and carcass fat were affected by stocking density. Interaction of B × D × S in thighs indicating that thighs of birds were affected differently in different sex, density and trimmed or untrimmed condition.…”
Section: Discussionmentioning
confidence: 99%